DIMENSI MANUSIA SEBAGAI OBJEK PENDIDIKAN AGAMA ISLAM - Muhammad Nur Salim (ANDRAGOGI, 2021)
In the view of islamic religion, human focus is only assessed from the intention (motiv), speech, and attitude or actions. Al Quran always mentions and discusses humans from the three factors that will always exist in humans. Even Allah SWT made a noble or despicable standard for humans only in terms of piety. Meanwhile, piety is defined as obedience to carry out religious orders and obedience to stay away from everything that is prohibited by religion. This paper intends to describe the dimensions of a human being when faced with religious law. With this paper, it is hoped that an educator can assess and observe his students and even himself; whether his intentions, words, attitudes or actions are synchronized and correct. As we know that a human being is required to be able to synchronize his heart, mouth, and mind / brain as well as his attitudes and actions. If these three things are not balanced (balance), then it can be ascertained that the person has problems in his life. And as a follower of religion, someone must have faith in the existence of God who is believed to be the All-Seer and All-Knower about all things including thoughts and heart whispers. With this paper, it is hoped that a person can describe his own dimension, both from the outer dimension and from his own inner side. Likewise, educators can assess their students from a physical and mental perspective so that students can be educated by educators who are competent in seeing all aspects of the dimensions of their students, even students can educate themselves and build awareness and protect them until the end of their lives.Keyword: human dimension, object, Islamic education AbstrakDalam pandangan agama Islam, manusia hanya fokus dinilai dari niat (motiv), ucapan, dan sikap atau perbuatannya. Al Quran selalu menyebut dan membahas manusia dari tiga faktor tersebut yang akan selalu ada dalam diri manusia. Bahkan Allah SWT membuat standar mulia atau hinanya manusia cuma dari segi ketakwaanya saja. Sedangkan takwa diartikan sebagai ketaatan untuk melaksanakan perintah agama dan ketaatan untuk menjauhi segala hal yang dilarang oleh agama. Tulisan ini bermaksud untuk menguraikan seperti apa dimensi seorang manusia apabila dihadapkan pada hukum agama. Dengan tulisan ini diharapkan seorang pendidik bisa menilai dan mengobservasi muridnya bahkan dirinya sendiri; apakah niat, ucapan, sikap atau perbuatannya sudah singkron dan benar. Sebagaimana kita ketahui bahwa seorang manusia dituntut untuk bisa mensingkronkan antara hati, mulut, dan akal/otak serta sikap dan perbuatannya. Jika sampai tiga hal tersebut tidak seimbang (balance) maka bisa dipastikan bahwa orang tersebut bermasalah dalam hidupnya. Dan sebagai penganut agama, seseorang pasti memiliki keyakinan akan eksistensi Tuhan yang diyakini sebagai Yang Maha Melihat dan Maha Mengetahui tentang segala hal termasuk pikiran dan bisikan hati. Dengan tulisan ini diharapkan seseorang bisa menguraikan akan dimensi dirinya sendiri baik dari dimensi lahir maupun dari sisi batinnya sendiri. Begitu juga para pendidik bisa menilai muridnya dari segi lahir maupun batin sehingga murid bisa dididik oleh pendidik yang berkompeten dalam melihat semua aspek dimensi muridnya bahkan murid bisa mendidik dirinya sendiri dan membangun kesadaran serta menjaganya sampai akhir hayat.Kata Kunci: dimensi manusia, objek, pendidikan agama Islam